In vivo morphine treatment synergistically increases LPS-induced caspase activity in immune organs - Olin, Michael (2010)
Apoptosis is an important mechanism for the elimination of infected cells, which would normally serve as hosts for further pathogen replication. Apoptosis is initiated through complex pathways involving a family of cysteine proteases known as caspases. The detection of apoptosis is essential for understanding the long-term health effects inflicted by the therapeutic use of opiate drugs such as morphine for pain treatment following major trauma or disease and abusive use of such drugs in addiction. Common practices of apoptosis detection involve the removal of tissues, which subsequently induce spontaneous apoptosis unrelated to the actual effects of the opioid drug exposure. The objective of this study was to develop an in vivo detection method for assessing morphine’s ability to directly induce apoptosis, and in the combination of morphine following an inflammatory response induced by lipopolysaccharide (LPS). Mice were administered saline, morphine, LPS, or a combination of morphine and LPS. Prior to sacrifice, mice were injected with a poly-caspase-specific apoptosis detection probe, to detect internal caspase activity in vivo. Administration of morphine alone did not directly induce apoptosis. However, morphine significantly enhanced the LPS induced apoptosis in splenocyte and bone marrow cells as well as in spleen, liver, and thymus tissues. The use of a poly-caspase detection probe methodology, to label apoptotic cells in vivo, provides a powerful quantitative tool for the in vivo analysis of caspase activity.